Measuring the evolution of bank credit volume on some macroeconomic variables in Iraq during 2004-2018 - Fatima Sawadi Shenbara; Jaber, Aqel Hameed; Jaber, Aqel Hameed (International Journal of Psychosocial Rehabilitation, 2020)
The current study was summarized to explain what was bank credit and the theories explaining it, as well as explain its impact on some macroeconomic variables during 2004-2018 in Iraq, the simple regression model and the 9EVIEWS software were used, the study reached several conclusions, especially since the government bias to deal with government banks, and ignore private banks, it also concluded that the monetary credit has weak effect on inflation, as a result of complete control in the latter by the monetary policy represented by the Central Bank of Iraq, the accumulation of liquidity at the commercial banks in Iraq, despite reaching high rates. The sector unable to operate and invest its assets and deposits it has, the study recommended that there were great investment plans and opportunities, provided by the environment, the Iraqi economy, helps commercial banks to invest the cash they have, and to achieve appropriate profitability, it will help to leave the exploitation unethical, for example the higher profit margin charge, as well as the bias that the government works with banks, it does not work for the Iraqi economy,it must move away from prejudice and leave government and private banks to compete, and make it work and diversify its sources of income, which depends mostly on the currency auction and the difference between the official and advertised price.